Adaptive evolution of stress response genes in parasites aligns with host niche diversity - Armando J. Cruz-Laufer; Maarten P. M. Vanhove; Lutz Bachmann; Maxwell Barson; Hassan Bassirou; Arnold R. Bitja Nyom; Mare Geraerts; Christoph Hahn; Tine Huyse; Gyrhaiss Kapepula Kasembele; Samuel Njom; Philipp Resl; et al. (BMC Biology)
Abstract Background Stress responses are key the survival of parasites and, consequently, also the evolutionary success of these organisms. Despite this importance, our understanding of the evolution of molecular pathways dealing with environmental stressors in parasitic animals remains limited. Here, we tested the link between adaptive evolution of parasite stress response genes and their ecological diversity and species richness. We comparatively investigated antioxidant, heat shock, osmoregulatory, and behaviour-related genes (foraging) in two model parasitic flatworm lineages with contrasting ecological diversity, Cichlidogyrus and Kapentagyrus (Platyhelminthes: Monopisthocotyla), through whole-genome sequencing of 11 species followed by in silico exon bait capture as well as phylogenetic and codon analyses. Results We assembled the sequences of 48 stress-related genes and report the first foraging (For) gene orthologs in flatworms. We found duplications of heat shock (Hsp) and oxidative stress genes in Cichlidogyrus compared to Kapentagyrus. We also observed positive selection patterns in genes related to mitochondrial protein import (H sp) and behaviour (For) in species of Cichlidogyrus infecting East African cichlids—a host lineage under adaptive radiation. These patterns are consistent with a potential adaptation linked to a co-radiation of these parasites and their hosts. Additionally, the absence of cytochrome P450 and kappa and sigma-class glutathione S-transferases in monogenean flatworms is reported, genes considered essential for metazoan life. Conclusions This study potentially identifies the first molecular function linked to a flatworm radiation. Furthermore, the observed gene duplications and positive selection indicate the potentially important role of stress responses for the ecological adaptation of parasite species.